Effectiveness of DNA Barcoding Primers in Red Algae (Rhodophyta) Identification - Khan, Aidil Zaid; Fernando, Ardian Putra; Pamungkas, Edo Agam; Andhira, Ayu; Ishlah, Rifa Nur; Resmi, Denia Dwi Citra; Damayanti, Farida; Rahmawati, Dewi (SEAMEO BIOTROP, 2025)
Red algae (Rhodophyta) are vital primary producers in marine ecosystems and are economically significant due to their wide use in food, pharmaceutical, and cosmetic industries. The significant utilization of red algae indicates that these organisms require conservation and protection from extinction, therefore, accurate identification is a must. Traditional morphological approaches face challenges due to their simplicity and plasticity; however, molecular techniques, such as DNA barcoding can overcome these limitations. This study evaluated the effectiveness of using ITS1, Cox2-3, rbcL 1, and rbcL 2 primers for barcoding seven red algae species, focusing on amplification success and sequencing quality. All of the above-mentioned primers have demonstrated a noteworthy amplification rate of success, with 100% efficacy observed for ITS1 and rbcL 2. However, only Cox2-3, rbcL 1, and rbcL 2 primers exhibited a high-quality read based on the sequencing quality score, indicating their reliability in capturing the target sequence for identification. The results strongly suggested that rbcL 2 is the optimal choice for identifying Rhodophyta due to its high amplification rate and high-quality sequencing results.